Assessing the socio-spatial effects of forest degradation in Kaimur Wildlife Sanctuary, Bihar, India - Shashi Bhushan; Sucharita Sen (Trees, Forests and People)
Forests are central to livelihoods in rural India, especially among marginalized groups living adjacent to protected areas. Socio-economic inequalities in accessing forest resources, however, are poorly understood, particularly between caste groups. This research investigates forest dependence and land use dynamics during the last four decades (1977–2022) of the Kaimur Wildlife Sanctuary, Bihar, India. Mixed methods combine remote sensing and GIS-based land use and land cover (LULC) analysis with socioeconomic surveys of 327 household samples, randomly selected using stratified random sampling. Results indicate a considerable loss of 382.68 km² (30.37 %) of forest cover, largely converted to fallow and agricultural land. Scheduled Tribes (ST) families have the highest forest dependence (>70 %), followed by Scheduled Castes (SC) (50 %), while Non-SC-ST groups depend more on agriculture. Statistical tests (p < < 0.05) reveal strong correlations among caste, land ownership, and forest dependence, with marginalized groups having lower access to resources because of forest degradation. Households in zones of moderate degradation have higher incomes from forest resources than those in high or low degradation, showing an inverted U-shaped dependency trend. When forest resources are in decline, marginalized groups are more pushed toward wage work and travel for longer distances to collect resources. The research highlights the imperative to ensure inclusive forest management policies, participatory conservation plans, and sustainable livelihood options. By addressing socio-economic disparities in forest access, this study adds to the wider literature on how to balance conservation and rural development.